On the Use of the Repeated-Sprint Training in Hypoxia in Tennis - Brechbuhl, Cyril; Brocherie, Franck; Willis, Sarah J.; Blokker, Thomas; Montalvan, Bernard; Girard, Olivier; Millet, Gregoire P.; Schmitt, Laurent (Frontiers in Physiology, 2020)
Purpose: To examine physiological and technical responses to repeated-sprint training in normobaric hypoxia at 3000 m (RSH, n=11) or in normoxia (RSN, n=11) compared to a control group (CON, n = 8) in well-trained tennis players. Participants were 28.8 ± 5.9 yrs old without any previous experience of training in hypoxia. Methods: In addition to maintaining their usual training (CON), both RSH and RSN groups completed five tennis specific repeated-shuttle sprint sessions (4 × 5 × 8-s maximal sprints with 22-s passive recovery and 5 min rest between sets) over 12 days. Before (Pre), the week after (Post-1) and three weeks after Post-1 (Post-2), physical/technical performance during Test to Exhaustion Specific to Tennis (TEST), repeated-sprint ability (RSA) (8 × 20 m shuttle runs – departing every 20-s) and heart rate variability (HRV) were assessed. Results: From Pre to Post-1 and Post-2, RSH improved TEST time to exhaustion (+18.2% and +17.3%; both P < 0.001), while the ‘onset of blood lactate accumulation’ at 4 mmol.L-1 occurred at later stages (+ 24.4% and +19.8%, both P < 0.01). At the same time points, ball accuracy at 100% V̇O2max increased in RSH only (+38.2%, P = 0.003 and +40.9%, P = 0.007). Markers of TEST performance did not change for both RSN and CON. Compared to Pre, RSA total time increased significantly at Post-1 and Post-2 (–1.9% and –2.5 %, P < 0.05) in RSH only and this was accompanied by larger absolute Δ total hemoglobin (+82.5% and +137%, both P < 0.001). HRV did not change either supine or standing positions. Conclusion: Five repeated sprint training sessions in hypoxia using tennis specific shuttle runs improve physiological and technical responses to TEST, RSA and accompanying muscle perfusion responses in well-trained tennis players.